Fungi that cause postharvest diseases in chayote (Sechium edule (Jacq.) Sw.) and their in vitro control. - Romero Velazquez, Siul D. (2015)
The fruit of chayote (Sechium edule (Jaqc.) Sw.) it is a vegetable of export of importance to Mexico and Costa Rica. The commercial process requires to accomplish high quality standards, which implies fruit healthy and free from defects. However, due to the high humidity conditions that develop inside the plastic packing, there have been several rejections from brokers due to the presence of fungal diseases. The aim of this work was to identify morphological (optical microscopy and scanning electron) and molecularly (PCR: Polimerase Chain Reaction) the species of the causal fungi of the main postharvest diseases of chayote fruits for export, as well as in vitro tests of the effectiveness of various commercial products as inhibitors of the growth of these fungi. The results show that Didymella bryoniae is the cause of “gummosis of cucurbits”, while Fusarium oxysporum and F. solani cause fusarium head blight or drowning of guides; these pathogens damage the basal and median part of marketable fruit, in addition to Chaetomium globosum as associate of the infectious process caused for Fusarium sp., as a non-pathogenic saprophyte. Bacillus subtilis, had an effective inhibition (0,01 mg.l-1 a.i.) in vitro tests against Didymella bryoniae, Fusarium oxysporum and F. solani. Tebuconazole-trifloxystrobin was the most effective fungicide against the first 2, with an LD50 value of 0,0116 and 0,0106 mg.l-1 respectively; not so against F. solani, where prochloraz was more effective, with a LD50 value of 0,0042 mg.l-1. These results contribute to the recognition of the most important fungal diseases in chayote and their prospects for control during the postharvest handling of fruits for export.